2015
DOI: 10.1016/j.celrep.2015.01.033
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mitochondrial DEAD-Box Protein DDX28 Resides in RNA Granules and Functions in Mitoribosome Assembly

Abstract: SUMMARY Human mitochondrial ribosomes are specialized in the synthesis of 13 proteins, which are fundamental components of the oxidative phosphorylation system. The pathway of mitoribosome biogenesis, the compartmentalization of the process and factors involved remain largely unknown. Here, we have identified the DEAD box protein DDX28 as an RNA granule component essential for the biogenesis of the mitoribosome large subunit (mt-LSU). DDX28 interacts with the 16S rRNA and the mt-LSU. RNAi-mediated DDX28 silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 48 publications
14
100
0
Order By: Relevance
“…These results were confirmed in cultured human cells although biochemical studies localized most of the protein in mitochondria [127]. DDX28 interacts with the 16S rRNA and the mtLSU [127], most probably with a helix in domain V [128]. RNAi-mediated DDX28 silencing in HEK293T cells does not affect mitochondrial mRNA stability, 16S rRNA processing or modification.…”
Section: Rna Helicasessupporting
confidence: 72%
See 2 more Smart Citations
“…These results were confirmed in cultured human cells although biochemical studies localized most of the protein in mitochondria [127]. DDX28 interacts with the 16S rRNA and the mtLSU [127], most probably with a helix in domain V [128]. RNAi-mediated DDX28 silencing in HEK293T cells does not affect mitochondrial mRNA stability, 16S rRNA processing or modification.…”
Section: Rna Helicasessupporting
confidence: 72%
“…GFP-fused DDX28 was detected in punctate structures in COS1 cell mitochondria, about half of which co-localized with, or were adjacent to the mitochondrial nucleoids [126]. These results were confirmed in cultured human cells although biochemical studies localized most of the protein in mitochondria [127]. DDX28 interacts with the 16S rRNA and the mtLSU [127], most probably with a helix in domain V [128].…”
Section: Rna Helicasessupporting
confidence: 62%
See 1 more Smart Citation
“…We show that three previously uncharacterized bona fide RNA granule proteins-two RNA helicases and one FASTKD family memberplay essential and apparently non-redundant roles in different aspects of mitochondrial ribosome assembly, and we identify the 16S rRNA as a target for two of them: DDX28 and FASTKD2. A role for DDX28 in mitoribosome assembly was also reported by Tu and Barrientos (2014) in this issue of Cell Reports. Our previous investigation of GRSF1, which binds to G-rich L-strand transcripts (Antonicka et al, 2013), showed that it is also required for ribosome assembly, as suppression of GRSF1 resulted in the accumulation of a mt-SSU subassembly and a decrease in mt-LSU content.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, selective depletion of RNR2 may occur due to its aberrant processing or due to ribosome misassembly. Indeed, recent studies suggest that failure to assemble RNR2 with mitochondrial ribosomal proteins leads to its selective depletion, which has been proposed to be mediated by the mitochondrial degradosome (Antonicka and Shoubridge 2015;Tu and Barrientos 2015). The levels of isoleucyl tRNA (TRNI), one of the heavystrand-encoded tRNAs highly enriched in FASTKD2-GFP libraries, are unaffected by depletion of FASTKD2 by RNAi and CRISPR/Cas9-mediated mutagenesis (Fig.…”
Section: Depletion Of Fastkd2 Affects the Levels Of Several Of Its Tamentioning
confidence: 99%